Age Differences in Non-Medical Prescription Opioid Use and Psychological Distress. (3rd August 2020) - Chan, Keith; Moller, Mary; Marsack-Topolewski, Christina; Winston, Priya; Jennings, Rubin; Prifti, Andriana
Abstract: Background/Purpose : Prescription opioid use has been recognized as an epidemic in the United States and globally. More research is needed to understand the association of opioids and mental health for older adults. This study examined age differences in the association of non-medical prescription opioid use (NMPOU) and psychological distress, with a focus on older adult populations. Methods : This study used the 2016 National Survey on Drug Use and Health (NSDUH), and included 37, 842 adults aged 18 and older. Weighted multiple regression and logistic regression analyses were used to examine the association of NMPOU and psychological distress, measured by the Kessler Psychological Distress Scale (K6). Results : NMPOU was associated with higher psychological distress ( b = 0.48, SE = 0.16, p < .01). For those 50 and older, NMPOU was associated with 224% increased odds of meeting the clinical threshold for having a serious mental illness (SMI; OR = 2.24, p < .01, 95% CI: 1.23, 4.09). Conclusions : Although the prevalence of NMPOU and psychological distress trended downward throughout the lifespan, the association of NMPOU on SMI was highest among the youngest and oldest adults. These findings highlight the need for services and supports that are tailored for older adult populations. Future research is needed to investigate vulnerabilities from life stage stressors specific to older adults, which may account for the disproportionate odds of opioid use on mental health pathology. Interprofessional collaboration is needed among geriatric professionals to provide effective mental health treatment for this at-risk population.